Fossil amphibians and reptiles from Plakias, Crete: A glimpse into the earliest late Miocene herpetofaunas of southeastern Europe - Georgalis, Georgios L. (2016)
Fossil amphibians and reptiles from the earliest late Miocene (early Tortonian, MN 9) of Plakias (Crete, Greece) are described in this paper. Most of the material is fragmentary, precluding precise taxonomic assignment. Nevertheless, the herpetofauna of Plakias is here shown to be diverse, comprising at least six different taxa: an alytid anuran, a crocodilian, two turtles (a pan-trionychid and a geoemydid) and two squamates (an amphisbaenian and a colubroid snake). The crocodilian material represents the first such fossils described from Greece and furthermore, one of the latest occurrences of this group in Europe. The pan-trionychid and the geoemydid represent the oldest occurrences of these groups in Greece and further add to their scarce Miocene record from this country. The first description of a fossil amphisbaenian from Greece is also provided. The new specimens from Plakias add to our knowledge of the Miocene herpetofaunas of southeastern Europe.